RISK ASSESSMENT OF EXTREME EVENTS IN ROMANIA - Ionela-Daniela Găitan (Botezatu) (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2020)
The increasing and severe occurrence of these events requires the implementation of adequate risk management systems. All developed countries focus on trying to prevent and mitigate such events. The most important stage in the risk management process is risk assessment. In this article is presented a conceptual approach to the risk assessment stage of extreme events and how the risk assessment stage of extreme events in Romania was performed. The purpose of this paper is to analyze the stage of risk assessment of extreme events in Romania. In this article, is used qualitative research based on data processing and analysis, documenting risk assessment methodologies, studying reference books and articles and synthesizing conclusions.